On the Significance of the Flow Model of Rumination for Transdiagnosis of Mental Disorders - Luyue ZHANG; Shuang CHENG; Haiyan FANG; Yuning LI; Jing CHEN; Tao ZOU (Yixue yu zhexue, 2025)
Transdiagnosis aims to identify and understand common factors and mechanisms among multiple mental disorders, which makes up for the limitations of traditional psychiatric classification system. The flow model of rumination fully embodies the research progress of transdiagnostic thinking. This paper reflects on the advantages and shortcomings of current transdiagnostic system, elaborates on the core structure and dynamic features of the rumination flow model, and discusses its theoretical, diagnostic, and clinical implications in transdiagnostic mental health research. The goal is to assist practitioners in adopting a transdiagnostic mindset to deepen their understanding of mental disorders from multiple perspectives, dimensions, and spectrums, ultimately contributing to the advancement of precision psychiatry.